MODEL ANTISIPASI TINDAKAN KEKERASAN DI SEKOLAH MENENGAH ATAS ( SMA) DI KABUPATEN CIANJUR MELALUI INTERNALISASIAN NILAI AGAMA, PANCASILA DAN BUDAYA KEARIFAN LOKAL - Cucu Solihah; Hilman Nur; Iis Ristiani (JURNAL HUKUM DE'RECHTSSTAAT, 2020)
Acts of violence that often occur among adolescents become very vulnerable and have an impact on the quality of a generation, for that we need a model of anticipating acts of violence in high school (SMA) in Cianjur Regency through internalization of religious values, Pancasila Cianjur local wisdom culture is three factors which is crucial for the success of the education process because it contains high and great values to be realized and imbued by the nation's generation.The aim is to foster the values of religious teachings, Pancasila and also the culture of local wisdom which began to fade behind high school students in Cianjur Regency with research methods using a qualitative approach, the values that exist in Religion, Pancasila and also the culture of local wisdom that must be upheld Cianur high by religious and cultured communities as part of citizens. The results and conclusions show that the factors of religion, Pancasila and Cianjur local wisdom culture are very important to convey to students at the high school level in Cianjur Regency as moral provisions, ethics of a nation's generation character so that acts of violence or anarchism can be anticipated early on.